DFT and TD-DFT Study of Structure and Properties of Semiconductive Hybrid Networks Formed by Bismuth Halides and Different Polycyclic Aromatic Ligands - Y. Belhocine; M. Bencharif (E-Journal of Chemistry)
The structure and spectroscopic properties of polycyclic aromatic ligands of 2,3,6,7,10,11-hexakis (alkylthio) triphenylene (alkyl: methyl, ethyl, and isopropyl; corresponding to the abbreviations of the molecules: HMTT, HETT and HiPTT) were studied using density functional theory (DFT) and time dependent density functional theory (TD-DFT) methods with triple-zeta valence polarization (TZVP) basis set. It was shown that the type of functional theory used, Becke-Perdew (BP) and Leeuwen-Baerends (LB94) implemented in Amsterdam Density functional (ADF) program package, does not have essential influence on the geometry of studied compounds in both ground and excited states. However, significant differences were obtained for the band gap values with relativistic effects of the zero order regular approximation scalar corrections (ZORA) and LB94 functional seems to reproduce better the experimental optical band gap of these systems.